Manajemen Pemasaran Pada Bank Sampah Syariah Secara Bertahap, Berkesinambungan dan Sistematis - Hidayatul Fajriya (Al-Musthofa: Journal of Sharia Economics, 2019)
The purpose of this study is to find out the marketing management in the Islamic Garbage Trash Bank (BSS) FEBI UINSA with all the obstacles. The research method used is qualitative research with a descriptive approach using triangulation of data in gathering information relating to marketing management of the Trash Bank with marketing managerial respondents from the Sharia Trash Bank. The results of the research are marketing management at the FEBI UINSA Sharia Trash Bank, namely by dividing into 3 stages namely long-term, medium-term and short-term in carrying out marketing strategies for the development of Sharia Trash Banks (BSS). Besides using promotional activities through socialization, BSS FEBI UINSA also conducts promotional activities through online and offline media. The marketing management of the Islamic Garbage Bank is still limited to the internal area of ​​FEBI UINSA, but does not rule out the possibility of developing it to external areas.